2012
DOI: 10.1021/ja307803m
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Imipenem and Meropenem by the RND-Transporter MexB Studied by Computer Simulations

Abstract: Basic understanding of the means by which multidrug efflux systems can efficiently recognize and transport drugs constitutes a fundamental step toward development of compounds able to tackle the continuous outbreak of new bacterial strains resistant to traditional antibiotics. We applied a series of computational techniques, from molecular docking to molecular dynamics simulations and free energy estimate methods, to determine the differences in the binding properties of imipenem and meropenem, two potent anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 108 publications
3
34
0
Order By: Relevance
“…Several studies evaluating compounds’ MICs indicated that MexAB-OprM affects the activity of MER, while that of IMI is essentially insensitive to over-expression of the pump [9699]. To identify the molecular basis of the underlying carbapenem–efflux-pump interactions Collu and co-workers performed docking and 8 standard 50ns-long MD simulations using a truncated model of MexB [92]. Configurations assumed by the compounds during the simulations are reported in Figure 4.…”
Section: Efflux Pump Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluating compounds’ MICs indicated that MexAB-OprM affects the activity of MER, while that of IMI is essentially insensitive to over-expression of the pump [9699]. To identify the molecular basis of the underlying carbapenem–efflux-pump interactions Collu and co-workers performed docking and 8 standard 50ns-long MD simulations using a truncated model of MexB [92]. Configurations assumed by the compounds during the simulations are reported in Figure 4.…”
Section: Efflux Pump Simulationsmentioning
confidence: 99%
“…Arrows denote the orientation of the compounds in panels a, b, and c. In panel d we report the shift of IMI. Adapted from [92], modified.…”
Section: Efflux Pump Simulationsmentioning
confidence: 99%
“…Their experiments produced an insight into the mechanism that MDR efflux pumps adopt in order to differentiate between their substrates from their inhibitors or modulating agents [119]. The transporter’s periplasmic domain identified two affinity binding sites that appeared to share multiple resemblances with the proximal and distal binding regions found in that of AcrB of E. coli , a close homologue of MexB.…”
Section: Structural and Computational Approaches To Develop Efflux Pumentioning
confidence: 99%
“…Applying MDS, along with free energy estimation methods and molecular docking produced results in good agreement with the experimental evidence of the carbapenems. It also highlights the important role played by the surrounding solvent in antibiotic transport as both imipenem and meropenem showed a high degree of solvation in both binding pockets [119]. …”
Section: Structural and Computational Approaches To Develop Efflux Pumentioning
confidence: 99%
“…Our database, freely accessible online, is to our knowledge the first extensive one including dynamical properties for a large set of compounds. Besides the specific application to the translocation of antibiotics through bacterial porins [28,29] and to their extrusion by efflux pumps [30,31], this piece of information can be useful for protein-ligand molecular docking [32], whose success rate is known to be strongly dependent on the generation of accurate input geometries and on the description of the flexibility of both partners involved in the binding process [33]. While receptor flexibility is nowadays routinely considered using different techniques [34][35][36], in the vast majority of docking campaigns, ligand flexibility is generally taken into account by considering the rotatable bonds of one given input structure, sometimes generating the 3D structure from 2D drawings or directly from SMILES strings [33].…”
Section: Introductionmentioning
confidence: 99%